2014
DOI: 10.18070/euiibfd.75843
|View full text |Cite
|
Sign up to set email alerts
|

Tüketi̇ci̇ Yeni̇li̇kçi̇li̇ği̇ Ve Algilanan Ri̇ski̇n Satin Alma Davranişina Etki̇si̇

Abstract: ÖZYenilikçi tüketiciler ürünün ilk kullanıcısı olmaları, ürün hakkında ilk geri bildirimleri paylaĢmaları ve potansiyel alıcılara ürünü tanıtıp bilgi sağlamaları gibi nedenlerle iĢletmeler ve akademisyenler için önemlidir. Bu çalıĢma tüketici yenilikçiliği, algılanan risk ve satın alma davranıĢı arasındaki iliĢkiyi araĢtırmıĢtır. GüdülenmiĢ tüketici yenilikçiliği ve algılanan risk ölçeklerinden faydalanılarak 402 örnekten toplanan veriler yapısal eĢitlik analizi kullanılarak incelenmiĢtir. AraĢtırma sonuçları … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Belbağ and Yılmaz (2017) reveal that consumers seeking for innovation and social identity positively and significantly affect product-based innovativeness. Bülbül and Özoğlu (2014) revealed that innovativeness has an increasing effect on the purchasing decision of the consumer and there is a positive relationship between consumer innovativeness and purchasing behavior, whereas there is a negative relationship between consumer innovativeness and perceived risk and between perceived risk and purchasing behavior. Aslay et al (2013), on the other hand, when examining whether there is a relationship between materialism and demographic characteristics, or how the direction of Özkan Pir this relationship is, they could not find any relationship between attaching importance to materiality and demographic variables.…”
Section: Discussionmentioning
confidence: 99%
“…Belbağ and Yılmaz (2017) reveal that consumers seeking for innovation and social identity positively and significantly affect product-based innovativeness. Bülbül and Özoğlu (2014) revealed that innovativeness has an increasing effect on the purchasing decision of the consumer and there is a positive relationship between consumer innovativeness and purchasing behavior, whereas there is a negative relationship between consumer innovativeness and perceived risk and between perceived risk and purchasing behavior. Aslay et al (2013), on the other hand, when examining whether there is a relationship between materialism and demographic characteristics, or how the direction of Özkan Pir this relationship is, they could not find any relationship between attaching importance to materiality and demographic variables.…”
Section: Discussionmentioning
confidence: 99%
“…Beliefs and attitudes of consumers enable the establishment of relationship between the goods and brands. Individuals determine their needs according to their beliefs and attitudes, and make the purchasing decision accordingly (Bülbül and Özoğlu, 2014).…”
Section: Paint Marketing and Factors Affecting The Consumers' Paint P...mentioning
confidence: 99%
“…2015) sağlık (Zhao vd., 2016;Sodano, 2018), kişisel (Kumar vd. 2009;Hossain, Prybutok, 2008;Bian, Forsythe, 2012;Bülbül, Özoğlu, 2014), etik ve yasal faktörler (Pozo vd., 2012;Capon vd., 2015;Zhao vd., 2016) ile nanoteknolojik ürün satın alma niyetleri (Bian, Forsythe, 2012;Gupta vd., 2015;Kim, Chung, 2011;Güzeloğlu, 2015)…”
Section: Anket Formunun Oluşturulmasıunclassified